Evaluating treatments and corresponding costs of prostate cancer patients treated within an inpatient or hospital-based outpatient setting. (February 2015) - Seal, Brian; Sullivan, Sean D; Ramsey, Scott; Asche, Carl V; Shermock, Kenneth M; Sarma, Syam; Zagadailov, Erin; Farrelly, Eileen; Eaddy, Michael
ABSTRACT : Aim: To describe treatments and cost of care for prostate cancer (PCa) in hospital-based outpatient and inpatient settings.Methods: Hospital encounters associated with PCa (ICD-9 codes 185, 233.4) and PCa-related treatment in a hospital claims database were included.Results: There were 211, 440 encounters for PCa between January 2006 and December 2010 (88, 151 inpatient and 123, 289 outpatient). Average cost per inpatient stay was US12, 286 versus US4364 per outpatient visit. Most common treatment during an inpatient stay and outpatient visit was surgery (57%) and radiation (76%), respectively. A total of 80% of outpatient visits and 69.9% inpatient stays were associated with a single treatment; remaining encounters were associated with ≥2 treatments.Conclusion: Costs are consistent with previous estimates; however, multimodal therapy is an emerging trend that may be related to greater costs in the future which may also be a challenge for hospital decision makers.